Wykorzystanie metod taksonomii i wielowymiarowej analizy porównawczej w ocenie jakości wyrobów - Pfeifer, Stanisław (An application of taxonomic and multidimensional comparative analysis methods in quality assessment of goods, 2008)
The methods enabling an objective and quantitative assessment of processes, objects or particular products may play an important role in improving the quality management and operating processes. This results, among other things, from the fact that the use of numerical data allows processes to be controlled more precisely and the obtained results to be compared uniquely. In this paper it is shown that the taxonomic and multidimensional comparative analysis methods can be used for objective assessment of goods. It was found that an assessment of goods within the same assortment group is in fact a classification scheme, i.e. an ordering made according to a specified algorithm. Goods belonging to the same assortment group can be considered as a set of objects of common or different features. The common features decide on belonging to the same assortment group and they can be considered to be substitutes, because they meet the same needs and are of similar function. In turn, differentiated features decide on various final assessments, as goods within the same groups are classified in a different way. Based on the selected taxonomic procedures a method for selecting diagnostic features, being one of the most important tasks in objective quality assessment, is presented. It was shown that the specified set of features, measuring methods, the normalization of measured values and merging the normalized values into a single quantity are all the fundamental elements leading to objective quality assessment for goods.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 185-194